Impacts of Recombinant Human Erythropoietin Treatment During Predialysis Periods on the Progression of Chronic Kidney Disease in a Large‐Scale Cohort Study (Co‐JET study). Issue 2 (27th August 2013) - Akizawa, Tadao; Saito, Akira; Gejyo, Fumitake; Suzuki, Masashi; Nishizawa, Yoshiki; Tomino, Yasuhiko; Tsubakihara, Yoshiharu; Akiba, Takashi; Hirakata, Hideki; Watanabe, Yuzo; Kawanishi, Hideki; Bessho, Masami; et al.
Abstract The effect of recombinant human erythropoietin (rHuEPO) treatment on the progression of chronic kidney disease (CKD) has not been fully evaluated in Japan. We therefore retrospectively evaluated this in a sub‐cohort of a prospective multicenter study to investigate optimal hemoglobin (Hb) level of CKD patients on hemodialysis (HD) treated with rHuEPO; Japan Erythropoietin Treatment Study for Target Hb and Survival (JET study). Effect of rHuEPO treatment during predialysis period to delay initiation of HD was retrospectively assessed in 2434 patients from the JET study comparing groups with and without rHuEPO treatment. The assessment was done by Cox proportional hazards regression analysis and inverse probability‐weighted (IPW) analysis to adjust for time‐dependent confounders. The weights used in the IPW analysis were calculated using a logistic model that included baseline confounders and time‐dependent variables. During the predialysis period, 71.7% (1746 patients) were treated with rHuEPO (mean Hb level of 8.7 g/dL at initiation of rHuEPO treatment). Covariates significantly associated with initiation of rHuEPO treatment were Hb level, serum creatinine level, age, diabetes, cardiac insufficiency, and hypertension. The adjusted hazard ratio for time until HD initiation under rHuEPO treatment was 0.272 (95% CI, 0.223–0.331; P < 0.001) in the Cox analysis and 0.63 (95% CI, 0.53–0.76; P < 0.0001) in the IPW analysis. This retrospective study suggests that rHuEPO treatment during the predialysis period has preventive effects on the progression of CKD although further prospective investigation on the efficacy is needed.